(untitled) (American Journal of Islam and Society, 2018)
In her critical essay, “The Omnipresent Male Scholar,”2 Professor Kecia Ali sets out to call attention to what she sees as the hegemonic privileging of the male scholarly perspective and the need to replace this with an academic landscape more reflective and accommodating of the experiences and scholarly vantage points of women. To this end, she profiles the works of several (Muslim) men in Islamic Studies (myself included) and highlights the various ways in which they omit, overlook, undervalue, or dismiss the topic of women or the scholarly views and interventions of female scholars. Her arguments are reiterated and expanded (this time without naming her targets) in her Ismail R. al-Faruqi Memorial Lecture delivered at the 2017 annual conference of the American Academy of Religion.3 The present essay aims to respond to Professor Ali’s assessment of my work, most specifically Islam and the Blackamerican (and to a lesser extent, Islam and the Problem of Black Suffering) alongside some of the broader issues she raises as part of her general critique. I will leave it to the other male scholars she profiles to respond to what she has to say about their work ...